Paracoccidioides brasiliensis Releases a DNase-Like Protein That Degrades NETs and Allows for Fungal Escape - Zonta, Yohan Ricci; Dezen, Ana Laura Ortega; Della Coletta, Amanda Manoel; Yu, Kaio Shu Tsyr; Carvalho, Larissa; Santos, Leandro Alves dos; Deprá, Igor de Carvalho; Kratofil, Rachel M.; Willson, Michelle Elizabeth; Zbytnuik, Lori; Kubes, Paul; Ximenes, Valdecir Farias; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Paracoccidioidomycosis is a systemic fungal disease, considered endemic in Latin America. Its etiological agents, fungi of the Paracoccidioides complex, have restricted geographic habitat, conidia as infecting form, and thermo-dimorphic characteristics. Polymorphonuclear neutrophils (PMNs) are responsible for an important defense response against fungus, releasing Neutrophil Extracellular Traps (NETs), which can wrap and destroy the yeasts. However, it has been described that some pathogens are able to evade from these DNA structures by releasing DNase as an escape mechanism. As different NETs patterns have been identified in PMNs cultures challenged with different isolates of Paracoccidioides brasiliensis, the general objective of this study was to identify if different patterns of NETs released by human PMNs challenged with Pb18 (virulent) and Pb265 (avirulent) isolates would be correlated with fungal ability to produce a DNase-like protein. To this end, PMNs from healthy subjects were isolated and challenged in vitro with both fungal isolates. The production, release, and conformation of NETs in response to the fungi were evaluated by Confocal Microscopy, Scanning Microscopy, and NETs Quantification. The identification of fungal DNase production was assessed by DNase TEST Agar, and the relative gene expression for hypothetical proteins was investigated by RT-qPCR, whose genes had been identified in the fungal genome in the GenBank (PADG_11161 and PADG_08285). It was possible to verify the NETs release by PMNs, showing different NETs formation when in contact with different isolates of the fungus. The Pb18 isolate induced the release of looser, larger, and more looking like degraded NETs compared to the Pb265 isolate, which induced the release of denser and more compact NETs. DNase TEST Agar identified the production of a DNase-like protein, showing that only Pb18 showed the capacity to degrade DNA in these plates. Besides that, we were able to identify that both PADG_08528 and PADG_11161 genes were more expressed during interaction with neutrophil by the virulent isolate, being PADG_08528 highly expressed in these cultures, demonstrating that this gene could have a greater contribution to the production of the protein. Thus, we identified that the virulent isolate is inducing more scattered and loose NETs, probably by releasing a DNase-like protein. This factor could be an important escape mechanism used by the fungus to escape the NETs action.